1990
DOI: 10.1080/00207149008414516
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Strategies in Hypnosis: Toward Resolving the Hypnotic Conflict

Abstract: 2 experiments were carried out to assess the relative contributions of dissociation and absorption as cognitive strategies employed by high and low hypnotizable Ss in responding successfully to hypnotic suggestions. Of special interest was the manner in which Ss deal with conflicting information typically inherent in hypnotic suggestions. In the first experiment, Ss rated their attentional focus and the involuntariness of their experience after responding to a number of hypnotic suggestions administered in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The ideomotor/absorption explanation of the effects of suggestion required that subjects focus attention on imaginings that are consistent with the suggestion and that they ignore, disregard, or avoid inconsistent ideas Spiegel & Spiegel, 1978). However, experimental studies showed that when instructed to do so, subjects could respond to suggestions while imagining the opposite of what was suggested (Bartis & Zamansky, 1990;Kirsch, Council, & Mobayed, 1987;Spanos, Weekes, & deGroh, 1984;Zamansky, 1977;Zamansky & Clark, 1986). Furthermore, although reports of goal-directed fantasies were correlated with hypnotic responsiveness, instructing people to generate goal-directed fantasies did not increase responsiveness reliably (Buckner & Coe, 1977;Lynn, Snodgrass, Rhue, & Hardaway, 1987;Spanos, 1971;Spanos & Barber, 1972).…”
Section: Intentional and Spontaneous Imagery In Hypnosis: The Phenomementioning
confidence: 86%
“…The ideomotor/absorption explanation of the effects of suggestion required that subjects focus attention on imaginings that are consistent with the suggestion and that they ignore, disregard, or avoid inconsistent ideas Spiegel & Spiegel, 1978). However, experimental studies showed that when instructed to do so, subjects could respond to suggestions while imagining the opposite of what was suggested (Bartis & Zamansky, 1990;Kirsch, Council, & Mobayed, 1987;Spanos, Weekes, & deGroh, 1984;Zamansky, 1977;Zamansky & Clark, 1986). Furthermore, although reports of goal-directed fantasies were correlated with hypnotic responsiveness, instructing people to generate goal-directed fantasies did not increase responsiveness reliably (Buckner & Coe, 1977;Lynn, Snodgrass, Rhue, & Hardaway, 1987;Spanos, 1971;Spanos & Barber, 1972).…”
Section: Intentional and Spontaneous Imagery In Hypnosis: The Phenomementioning
confidence: 86%
“…When the state of hypnosis theory was last reviewed in this journal , a theoretical consensus was emerging based on the idea that focused attention, absorption, and involved imagining were central to hypnotic responding (E. R. Hilgard, 1975; J. R. Hilgard, 1970;Spiegel & Spiegel, 1978;Tellegen & Atkinson, 1974). Unfortunately, the emergent consensus was soon shattered by data indicating that participants could respond to suggestion while imagining conflicting events (Bartis & Zamansky, 1990;Kirsch, Council, & Mobayed, 1987;Spanos, Weekes, & DeGroh, 1984;Zamansky, 1977;Zamansky & Clark, 1986). Furthermore, although it has long been widely acknowledged that imagination plays a role in hypnotic responding, the relation between measures of imaginative traits (e.g., absorption) and hypnotic responsiveness is quite small (reviewed in .…”
Section: Irving Kirschmentioning
confidence: 99%
“…To our knowledge, this comparison has never been made, perhaps because of the consensual view that involved imagining mediates effects suggested during hypnosis. However, three studies reported by Zamansky and his colleagues (Bartis & Zamansky, 1990;Zamansky, 1977;Zamansky & Clark, 1986) and one reported by Spanos, Weekes, and de Groh (1984) present a strong challenge to this view. In these studies, participants were instructed to imagine a state of affairs that opposed or contradicted the suggested experience or behavior (e.g., people were asked to imagine bending an arm after hypnotic suggestions had rendered it stiff and rigid).…”
mentioning
confidence: 98%